1992
DOI: 10.1128/jvi.66.10.5890-5897.1992
|View full text |Cite
|
Sign up to set email alerts
|

A novel Ets-related transcription factor, Elf-1, binds to human immunodeficiency virus type 2 regulatory elements that are required for inducible trans activation in T cells

Abstract: Human immunodeficiency virus type 1 (HIV-1) and HIV-2 are structurally related retroviruses which both cause AIDS in humans. Although both viruses establish latency in quiescent human-peripheral-blood T cells, the asymptomatic phase of HIV-2 infection may be more prolonged than that of HIV-1. The latent phases of both HIV-1 and HIV-2 infection have been shown to be disrupted by T-cell activation, a process that requires host cell transcription factors. In the case of HIV-1, the transcription factor NF-KB is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 43 publications
2
62
0
Order By: Relevance
“…A 75 bp oligonucleotide (5'-gatctACTCTGCACAGAATGAGTAACTCACTCT-CTGCACAGAATGAGTAACTCACTCTGCACAGAATGAGTAACTCt-3'), representing three copies of the mouse 3' enhancer ETS-AP-1 motif, was cloned into the Bgl-XbaI site of the pP34SV3 vector (Mason et al, 1985) and is referred to as ETS-AP-1-1. The expression/in vitro translation vector containing the human Elf-I cDNA (312-1926 bp;Thompson et al, 1992) and full-length Ets-I cDNA (Wang et al, 1992) have been described previously. The c-Fos and Jun-B expression plasmids were kind gifts from Drs T.Kouzarides and K.Xanthopoulos, respectively.…”
Section: Plasmidsmentioning
confidence: 99%
“…A 75 bp oligonucleotide (5'-gatctACTCTGCACAGAATGAGTAACTCACTCT-CTGCACAGAATGAGTAACTCACTCTGCACAGAATGAGTAACTCt-3'), representing three copies of the mouse 3' enhancer ETS-AP-1 motif, was cloned into the Bgl-XbaI site of the pP34SV3 vector (Mason et al, 1985) and is referred to as ETS-AP-1-1. The expression/in vitro translation vector containing the human Elf-I cDNA (312-1926 bp;Thompson et al, 1992) and full-length Ets-I cDNA (Wang et al, 1992) have been described previously. The c-Fos and Jun-B expression plasmids were kind gifts from Drs T.Kouzarides and K.Xanthopoulos, respectively.…”
Section: Plasmidsmentioning
confidence: 99%
“…Elf-1 is the first Ets family protein known to interact with NF-κB family members (73). Mapping of the Elf-1 interaction domain with c-Rel revealed that the Ets domain is necessary and sufficient to mediate this interaction (74).…”
Section: Nf-κ κB and The Il-2 Receptormentioning
confidence: 99%
“…The trans-acting factors responsible for transcription for Pz2 remain to be determined. Potential candidates include proteins that bind to purine-rich regions of DNA such as NFAT (38,39), Ikaros (40,41), and members of the Ets family of transcription factors (27,42,43). All of these are known to be involved in the regulation of lymphoid genes.…”
Section: #1 (Pzl)mentioning
confidence: 99%